2003
DOI: 10.1111/j.1348-0421.2003.tb03374.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Relationship of PFGE Patterns of Moraxella catarrhalis between Hospital‐ and Community‐Acquired Respiratory Infections in a Community Hospital

Abstract: Moraxella (Branhamella) catarrhalis is an aerobic gram-negative, oxidase positive diplococcus, and was once considered a nonpathogenic commensal of the upper respiratory tract. However it has been regarded as a potential pathogen since the mid-1980s (6). In many countries, M. catarrhalis has become the third most common cause of bacterial lower respiratory tract infection after Haemophilus influenzae and Streptococcus pneumoniae (3). In general, M. catarrhalis is also recognized as a major cause of community-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
3
8
1
Order By: Relevance
“…Also, automated ribotyping failed to demonstrate its usefulness as an epidemiologic test for M. catarrhalis. PFGE was very effective in discriminating between isolates, as has been observed in an earlier study (12). Clonal spread among community-acquired isolates producing BRO-1 and BRO-2 was evident, even from this small sample of North American M. catarrhalis strains.…”
supporting
confidence: 80%
“…Also, automated ribotyping failed to demonstrate its usefulness as an epidemiologic test for M. catarrhalis. PFGE was very effective in discriminating between isolates, as has been observed in an earlier study (12). Clonal spread among community-acquired isolates producing BRO-1 and BRO-2 was evident, even from this small sample of North American M. catarrhalis strains.…”
supporting
confidence: 80%
“…Our previous national survey had already demonstrated that the Taiwan19F clone was spreading widely in Japan (30), which suggested that the causative pathogen spreading between NPI patients and outpatients might have originated from the same parent strain. A previous study indicated that there was some association between hospital-and community-acquired respiratory infections caused by Moraxella catarrhalis (20). In this study, we detected pattern A in the serotype 19F group in both NPI patients and outpatients, as well as pattern d in the serotype 23F group, indicating that some association existed between NPI patients and outpatients even in pneumococcal infection.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies conducted to determine the antimicrobial susceptibilities of isolates from NPI found that a high percentage of pneumococcal pathogens had multidrug resistance, including resistance to new quinolones (4,5,28,39). Masaki et al reported a possible relationship between the pulsed-field gel electrophoresis (PFGE) patterns of Moraxella catarrhalis isolates from hospital-and community-acquired respiratory infections in a community hospital (20). Yet there still is not sufficient evidence to determine whether a similar pattern exists for S. pneumoniae.…”
mentioning
confidence: 99%
“…13 (19,25,27). Some studies reported that infants and children were colonized by M. catarrhalis at a higher rate than only 1-5% healthy adults did (21), but isolates from older patients were more likely to be pathogenically significant (32) (15,19).…”
Section: T a B L E 2 Ml S T Al L E L I C P R O F I L E S O F S E L mentioning
confidence: 99%
“…M. catarrhalis also plays an important role in nosocomial respiratory infection (NRI) (4,14,19,20) (17,19,25,26,31,33) (2,18,29), thus it has a great sensitivity due to its ability to detect neutral genetic variations (8,22). MLST has been successfully widely used for analysis of many common pathogens such as Neisseria meningitidis, S. pneumoniae, Staphylococcus aureus, Streptococcus pyogenes, and Campylobacter jejuni (6,7,9,10) …”
Section: Introductionmentioning
confidence: 99%